Advancing Public Education in Pakistan through a Teacher Exchange Program in the United States - Madeline Milian, Sajid Ali Yousafzai (PJE, 2023)
This study examined a multi-year teacher exchange program that included Pakistani secondary English teachers and took place at a mid-sized institution of higher education in a western state in the United States. It aimed to understand the program’s possible impact on advancing Pakistan’s public education after the completion of the program. A major goal of the study was to analyze how participating secondary English educators in the program viewed, interpreted, andcould transform the new knowledge and strategies learned in the program into effective practices in their Pakistani educational settings